Characteristics Of Trust Among Successful Entrepreneurs In The Catering Services Industry In Malaysia - Suhaila Nadzri; Siti Syuhada Abd Rahman; Mohamad Sabri Haron; Salmy Edawati Yaacob; Nuradli Ridzwan Shah Mohd Dali (Center for Promoting Ideas, USA, 2024)
Indexed by ERA